2020
DOI: 10.1128/msystems.00357-19
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Microbial Community Networks with Incremental Organic Loading Rates Underlie Higher Anaerobic Digestion Performance

Abstract: Although biotic interactions among members of microbial communities have been conceived to be crucial for community assembly, it remains unclear how changes in environmental conditions affect microbial interaction and consequently system performance. Here, we adopted a random matrix theory-based network analysis to explore microbial interactions in triplicate anaerobic digestion (AD) systems, which is widely applied for organic pollutant treatments. The digesters were operated with incremental organic loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The study found strong positive correlations between RAS flow rate and influent flow rate (ρ = 0.65 and r = 0.71), RAS flow rate and inf‐BOD (ρ = 0.65 and r = 0.68), and influent flow rate and inf‐BOD (ρ = 0.61 and r = 0.59) (Figure 3). These results suggest that RAS flow rate could serve as an indirect indicator of the organic load of the sludge, affecting biogas production (Wu, Shan, et al, 2020). This finding is consistent with previous research showing that the organic loading rate of feedstock in the AD process is useful in ensuring its performance and stability (Bi et al, 2019; Ferguson et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The study found strong positive correlations between RAS flow rate and influent flow rate (ρ = 0.65 and r = 0.71), RAS flow rate and inf‐BOD (ρ = 0.65 and r = 0.68), and influent flow rate and inf‐BOD (ρ = 0.61 and r = 0.59) (Figure 3). These results suggest that RAS flow rate could serve as an indirect indicator of the organic load of the sludge, affecting biogas production (Wu, Shan, et al, 2020). This finding is consistent with previous research showing that the organic loading rate of feedstock in the AD process is useful in ensuring its performance and stability (Bi et al, 2019; Ferguson et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“… An overview of the visual encodings used to display classification method results and interactions between taxa; (A) taxa interaction network ( Wu et al, 2020 ), (B) taxa interaction network visualized using TDA in TMAP ( Liao et al, 2019 ), (C) visual representation of the results of the Random Forest classifier in BiomMiner ( Shamsaddini et al, 2020 ). …”
Section: Resultsmentioning
confidence: 99%
“…Analysis-Depending on the type of sequencing, different programs and methods can be used for functional profiling. (Wu et al, 2020), (B) taxa interaction network visualized using TDA in TMAP (Liao et al, 2019), (C) visual representation of the results of the Random Forest classifier in BiomMiner (Shamsaddini et al, 2020).…”
Section: Functional Profilingmentioning
confidence: 99%
“…To detect warming effects on potential fungal interactions, we used functional gene data to construct functional molecule ecological networks (fMENs) for control and warmed samples separately, via the pipeline of Molecular Ecological Network Analyses (MENA) (http://ieg4.rccc.ou.edu/mena/) (Wu et al, 2020). Only functional genes detected in all six biological replicates were included to ensure network reliability.…”
Section: Methodsmentioning
confidence: 99%